PS-C27-3: MEASURING ANTIHYPERTENSIVE DRUG CONCENTRATIONS TO DETERMINE NON-ADHERENCE IN HYPERTENSIVE PATIENTS WITH AND WITHOUT KIDNEY TRANSPLANTATION. (January 2023) - Peeters, Laura EJ; Hesselink, Dennis A; de Winter, Brenda CM; Lafeber, Melvin; Severs, David; van den Hoogen, Martijn WF; Sonneveld, Michelle AH; Ramakers, Chris RB; Bahmany, Soma; van Gelder, Teun; Koch, Birgit CP; Versmissen, Jorie
Abstract : Introduction: Non-adherence to antihypertensive drugs (AHDs) is one of the main causes of resistant hypertension which is defined as uncontrolled blood pressure despite the prescription of at least 3 AHDs. Objectives: Our primary objective was to determine the prevalence of non-adherence to AHDs in patients visiting the nephrology and vascular outpatient clinics. Inclusion rates at both departments allowed comparison between non-adherence of kidney transplantation (KT) patients with patients without KT as secondary objective. Design and method: This was a prospective observational study called RHYME-AD (Resistant Hypertension: MEasure Antihypertensive Drugs, MEC-2020–0096). Patients were eligible if they used at least 2 AHDs that could be measured with a validated UPLC-MS/MS method and had an office blood pressure > 140 and/or 90 mmHg. After informed consent was signed, rest material was collected from a regular venipuncture measurement. The total absence of drug in blood (<lower limit of detection) was defined as non-adherent. We made comparisons between patients with and without KT and with and without resistant hypertension, defined as an office blood pressure > 140 and/or 90 mmHg despite the use of 3 or more AHDs. Results: Material was available from 143 patients of which 93 had a KT and 66 patients fulfilled the definition of resistant hypertension. The overall adherence rate was 78.3%. From the non-adherent patients 87.8% was partially non-adherent and 12.2% non-adherent for all prescribed AHDs. When looking at the two separate groups, with and without KT, more patients in the non-KT cohort fulfilled the definition of resistant hypertension as compared to the KT-cohort (62.0% vs 37.6%, p = 0.005). There was a significant difference between having resistant hypertension and being non-adherent (non-adherence RH vs non-RH, 31.8% vs 13.0%, p = 0.023) and having KT and being non-adherent (non-adherence KT vs non-KT, 14.0% vs 36.0%, p = 0.005). In addition, patients with KT and no resistant hypertension were the most adherent to AHDs (91.2%). Conclusions: Hypertensive patients with a KT are less likely to be non-adherent to their AHDs as compared to hypertensive patients without a KT. However, patients fulfilling the definition of having resistant have a higher risk of being non-adherent to AHDs.